Shear resistant mechanisms in steel fiber reinforced concrete beams: An analytical investigation. (May 2022) - Singh Negi, Bichitra; Jain, Kranti
Abstract: In Steel fibre reinforced concrete (SFRC) beams, the total shear force is resisted by four resisting mechanisms viz., compressed concrete in the compression zone, aggregate interlocking through the aggregate interface at the critical diagonal crack, dowel action by the longitudinal tension reinforcement and steel fibers bridging the critical diagonal crack. It is complex to quantify the contribution of aggregate interlock and steel fibers because they perform in the same region at a diagonal crack. All four shear resisting mechanisms are interrelated, so there is the need for a mechanics-based model which can give a correct solution for quantifying the contribution of each. A mechanics-based mathematical model considering the effect of all shear resisting mechanisms has been proposed to predict the shear strength of steel fiber reinforced concrete beam (without transverse reinforcement). The efficacy of the proposed model has been verified through a large set of databases and found that it gives good correlations with the experimental results with mean, standard deviation and coefficient of variation obtained as 0.94, 0.22 and 22.99%, respectively. Also, the contribution of each shear resisting mechanism has been recommended.